Modeling the kinetics nonenzymatic browning reactions and rheological behavior in the termal process of fruit juices and pulps - Manayay, Damian (2010)
In the manufacture of fruit juices and pulps, is of paramount importance to refer to non-enzymatic browning and rheological behavior. The non-enzymatic browning is a phenomenon of darkening of a purely chemical (Braverman, 1980), is characterized by the presence of brown polymers called melanoidins, generated by the Maillard reaction or condensation of melanoidins, the caramelization and degradation of acid ascorbic, while the rheological behavior is define as the proportion deformation of the material when exposed to shear stress (σ) caused by a rheometer (Muller, 1978; Ibarz, 2005). Modeling studies of colour formation and definition of rheological behavior, considered in this review, aimed at the conclusion of the existence of a zero kinetic and first order respectively, and the most influential factors with the reactions are mainly Maillard, temperature, amino acids presence, water activity and pH, while the rheological behavior is affected by temperature, solid concentration and particles size that make up the suspension in the specific case of the pulps.